2020
DOI: 10.7759/cureus.9193
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Correlation of Ocular Surface Disease Index Scores in a Non-Clinical Population: The Karachi Ocular Surface Disease Study

Abstract: Introduction There is increasing recognition of dry eye disease (DED) as a significant factor influencing quality of life in seemingly normal individuals. Our goal was to determine the distribution of Ocular Surface Disease Index (OSDI) scores in non-clinical individuals in Karachi, Pakistan. Methods We distributed OSDI questionnaires to subjects aged > 18 years with no active ocular complaint. Examiners were selected from various areas of the city to administer questionnaires … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
(32 reference statements)
1
2
0
Order By: Relevance
“…The crude prevalence of dry eye symptoms in the sample was 65% (95% CI: 62%-75%), this prevalence is in line with previous studies (Bakkar et al, 2016;Hashmani et al, 2020;Shanti et al, 2020). For example, using a cut-off for the OSDI similar to ours (score 13), Hashmani and colleagues found a prevalence of symptoms of dry eye amongst 2433 respondents to be 64.4%.…”
Section: Discussionsupporting
confidence: 88%
“…The crude prevalence of dry eye symptoms in the sample was 65% (95% CI: 62%-75%), this prevalence is in line with previous studies (Bakkar et al, 2016;Hashmani et al, 2020;Shanti et al, 2020). For example, using a cut-off for the OSDI similar to ours (score 13), Hashmani and colleagues found a prevalence of symptoms of dry eye amongst 2433 respondents to be 64.4%.…”
Section: Discussionsupporting
confidence: 88%
“…The Tear Film and Ocular Surface Society, Dry Eye Workshop II indicated that the difference between sexes in symptomatic patients becomes a statistically significant risk factor only in older populations (50 years old and above) [ 9 ]. However, the Karachi Ocular Surface Study of 2433 non-clinical individuals showed no significant relationship between being female and having DED, even after excluding the younger population and analyzing only individuals aged 45 years and older [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a result of this study, aging is associated with a higher OSDI score (p<0.05). In one study, individuals' age has been a risk factor for higher OSDI scores (Hashmani et al, 2020). When the age group graphed the OSDI score, it showed a significant increment in OSDI score from the third to fourth decade of life, followed by a constant increase.…”
Section: Discussionmentioning
confidence: 98%